Bet 1: Can induced hypertension improve outcome following acute traumatic spinal cord injury?. Issue 4 (20th March 2018) - Bertram-Ralph, Elliott; Horner, Daniel
Abstract : A shortcut review was carried out to establish whether augmentation of blood pressure to a high mean arterial pressure (MAP) target in the early phase of traumatic spinal cord injury (SCI) could lead to improvements in morbidity or mortality. 23 directly relevant papers were found using the reported search strategy. Of these, two systematic reviews collated the best evidence to answer the clinical question. The author, date and country of publication; patient group studied; study type; relevant outcomes; results and study weaknesses of the best papers are tabulated. It is concluded that data from observational cohort studies support high MAP targets and avoidance of hypotension in the early stages of traumatic SCI, but there are insufficient trial data to support routine use as best practice. Given the intervention carries risk, induced hypertension requires careful consideration on a case-by-case basis.